Problems of Online Deposit Service Providers (JASTIP) (Jastip Onty Case Study) - Sitti Fausia; Hadi Tuasikal; Dwi Pratiwi Markus (Publikasi Indonesia, 2024)
Significant technological developments not only have an impact on the ease of access by the public as consumers of goods/services but also open up new business opportunities for business actors such as business opportunities in the field of e-commerce, namely the Jastip business or deposit services. Business actors often experience problems in the process of implementing their business. Some of the main problems or problems that are often found by just providers as business actors include related, unilateral cancellation from consumers, unclear information on goods, delivery of prohibited goods, and consumer dissatisfaction. This research aims to be an effective solution for just business actors in improving the online buying and selling experience for consumers and business actors. The research method carried out is descriptive field research that describes the results of research with a legislative approach as library data and interviews with business actors and just consumers as supporting data. The problematic settlement experienced by just providers in the implementation of their business has been supported by various laws and regulations in Indonesia, such as the Civil Code, government regulations and the Consumer Protection Law, this aims to protect consumer rights and ensure fair and transparent transactions. Non-compliance with these rules can result in legal and administrative sanctions for business actors.